2017
DOI: 10.1105/tpc.17.00542
|View full text |Cite
|
Sign up to set email alerts
|

The Tomato DELLA Protein PROCERA Acts in Guard Cells to Promote Stomatal Closure

Abstract: Plants employ stomatal closure and reduced growth to avoid water deficiency damage. Reduced levels of the growth-promoting hormone gibberellin (GA) lead to increased tolerance to water deficit, but the underlying mechanism is unknown. Here, we show that the tomato () DELLA protein PROCERA (PRO), a negative regulator of GA signaling, acts in guard cells to promote stomatal closure and reduce water loss in response to water deficiency by increasing abscisic acid (ABA) sensitivity. The loss-of-function mutant exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
117
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 67 publications
2
117
1
Order By: Relevance
“…Previously we showed that all double mutants exhibit reduced whole plant transpiration (Illouz-Eliaz et al, 2019). Here we examined whole-plant transpiration in irrigated M82 and gid1a mutant plants grown in a greenhouse using an array of load cells (lysimeters) which simultaneously followed the daily weight loss of each plant (Nir et al, 2017). Daily transpiration, transpiration rate and whole canopy conductance of gid1a were significantly lower than that of M82 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously we showed that all double mutants exhibit reduced whole plant transpiration (Illouz-Eliaz et al, 2019). Here we examined whole-plant transpiration in irrigated M82 and gid1a mutant plants grown in a greenhouse using an array of load cells (lysimeters) which simultaneously followed the daily weight loss of each plant (Nir et al, 2017). Daily transpiration, transpiration rate and whole canopy conductance of gid1a were significantly lower than that of M82 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To remove residues of buffer and cell particles, the tubes were centrifuged at 4°C for 5 min at 2200 rpm. Samples of digested epidermal strips were stained with neutral red, and cell vitality was examined microscopically (Nir et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining rigorous physiological studies in tomato with genetic/misexpression analysis, Nir et al (2017) were able to do just that. Conveniently, unlike Arabidopsis thaliana, which contains five DELLA genes, tomato has only one, PROCERA (PRO).…”
mentioning
confidence: 99%
“…Wild-type (M82), sit, 35S pro :proΔ17 (proΔ17), and 35S pro :proD17 plants in the sit background (proΔ17 sit) grown under a normal irrigation regime (1 irrigation) or without irrigation for 7 d. After 7 d without irrigation, the plants were rehydrated and recovery was assessed 10 d later. (Reprinted from Nir et al [2017], Figure 4A.) OPEN Articles can be viewed without a subscription.…”
mentioning
confidence: 99%